Dopamine D1 and D2 Receptors Are Important for Learning About Neutral-Valence Relationships in Sensory Preconditioning - Roughley, Stephanie; Marcus, Abigail; Killcross, Simon (Frontiers in Behavioral Neuroscience, 2021)
Dopamine neurotransmission has been ascribed multiple functions with respect to both motivational and associative processes in reward-based learning, though these have proven difficult to tease apart. In order to better describe the role of dopamine in associative learning, this series of experiments examined the potential of dopamine D1- and D2-receptor antagonism (or combined antagonism) to influence the ability of rats to learn neutral valence stimulus-stimulus associations. Using a sensory preconditioning task, rats were first exposed to pairings of two neutral stimuli (S2-S1). Subsequently, S1 was paired with a mild foot shock and resulting fear to both S1 (directly conditioned) and S2 (preconditioned) was examined. Initial experiments demonstrated the validity of the procedure in that measures of sensory preconditioning were shown to be contingent on pairings of the two sensory stimuli. Subsequent experiments indicated that systemic administration of dopamine D1- or D2-receptor antagonists attenuated learning when administered prior to S2-S1 pairings. However, administration of a more generic D1R/D2R antagonist was without effect. These effects remained constant regardless of the affective valance of the conditioning environment, and did not differ between male and female rats. The results are discussed in the context of recent suggestions that dopaminergic systems encode more than a simple reward prediction error, and provide potential avenues for future investigation.